Bio-functionalization of multi-walled carbon nanotubes - Majumder, Anindya; Khazaee, Maryam; Opitz, Joerg; Beyer, Eckhard; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (Physical Chemistry Chemical Physics, 2013)
Here we present a hybrid approach to functionalize multi-walled carbon nanotubes in aqueous solution, exploring a non-covalent binding strategy. We focus on formation of hybrid complexes consisting of carbon nanotubes decorated by single stranded DNA, non-covalently attached using surfactants as intermediate layers. Unlike single walled carbon nanotubes, revealing easy side wall wrapping of DNA, we observe that wrapping of nucleic acids around multi-walled carbon nanotubes is diameter dependent. © 2013 the Owner Societies.
CRIS-Team Scopus Importer:2023-03-20